2013
DOI: 10.1111/febs.12244
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial screening via large‐scale purification of Plasmodium falciparum Ca2+ATPase 6 and in vitro studies

Abstract: The most severe form of human malaria is caused by the parasite Plasmodium falciparum. Despite the current need, there is no effective vaccine and parasites are becoming resistant to most of the antimalarials available. Therefore, there is an urgent need to discover new drugs from targets that have not yet suffered from drug pressure with the aim of overcoming the problem of new emerging resistance. Membrane transporters, such as P. falciparum Ca2+‐ATPase 6 (PfATP6), the P. falciparum sarcoplasmic/endoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(85 reference statements)
0
4
1
Order By: Relevance
“…After overexpression, the purification yield of PfATP6 is similar to that of the rabbit Serca1a, and although the two proteins share a rather high degree of sequence similarity they exhibit significant differences with respect to their sensitivity to known SERCA inhibitors, e.g., thapsigargin and cyclopiazonic acid (Cardi et al 2010b;Arnou et al 2011). At variance with studies from others, our work demonstrated that PfATP6 is probably not the target of the antimalarial drug artemisinin; recently, our purified recombinant PfATP6 was used for screening from a compound library inhibitors that might potentially be used as new antimalarial drugs (David-Bosne et al 2013).…”
Section: Discussioncontrasting
confidence: 49%
“…After overexpression, the purification yield of PfATP6 is similar to that of the rabbit Serca1a, and although the two proteins share a rather high degree of sequence similarity they exhibit significant differences with respect to their sensitivity to known SERCA inhibitors, e.g., thapsigargin and cyclopiazonic acid (Cardi et al 2010b;Arnou et al 2011). At variance with studies from others, our work demonstrated that PfATP6 is probably not the target of the antimalarial drug artemisinin; recently, our purified recombinant PfATP6 was used for screening from a compound library inhibitors that might potentially be used as new antimalarial drugs (David-Bosne et al 2013).…”
Section: Discussioncontrasting
confidence: 49%
“…In comparison, cyclopiazonic acid (CPA; 10 μM), an established inhibitor of PfATP6 (ref. 37 ), induced a strong Ca 2+ responses in the parasite's cytoplasm ( Supplementary Fig. 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given that ebselen has previously been reported to inhibit PfATP6 and the H + ,K + -ATPase (13, 14), this compound is likely an unspecific P-type ATPase inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen is known to inhibit the mammalian H + ,K + -ATPase (13) and the Ca 2+ -ATPase ATP6 of Plasmodium falciparum (PfATP6), in addition to Pma1 (14). Due to the reactivity of ebselen with protein thiols, it is believed to target several enzymes and modify a range of biological activities (15).…”
Section: Introductionmentioning
confidence: 99%